Problem-Based Learning (PBL): Abdominal Pain in a Pregnant Woman - Jennifer Koestler; Eva Waite; Michael Chietero; Joanna Shulman; Suzanne Rose; Edward Poliandro; Virginia Walther; William Simpson; Ana Nunez (Association of American Medical Colleges, 2009)
Abstract This case, which evolves over three sessions, describes the course of a pregnant woman from the Dominican Republic who presents to the emergency department complaining of abdominal pain. Developed by faculty from multiple clinical departments, this case allows learners to integrate and apply collected data to problem-solve. It also helps students develop the skills necessary for the interpretation and utilization of relevant historical, physical examination, and laboratory information in a patient who is acutely ill. Topics addressed in the exercise include symptom presentation/evolution, generation of differential diagnosis, diagnostic testing, and patient management. The exercise reiterates the clinical relevance of basic science topics, including embryology, anatomy, pharmacology, physiology, and pathophysiology. It also allows students to address culture, intimate partner violence, health beliefs, population medicine, and evidenced-based practice. The problem-based format fosters self-directed learning, reflection, and collaborative practice. Student evaluations have consistently indicated that the exercise has helped them to think about a clinical case in a multidisciplinary fashion, across specialty lines, and from a cultural perspective. Since first implementing this case in 2003, we have recognized the benefit of having fourth-year students cofacilitate the exercise. We have also involved the medical library staff in the implementation of this exercise to provide students with an additional resource to help them with more challenging literature searches. This problem-based learning exercise allows third-year medical students to consolidate educational experiences from across their clerkships and encourages multidisciplinary thinking in their clinical interactions. The strength of the case is that students are required to think outside the context of a specific clerkship and integrate symptoms across organ systems.